Pupillary diameter and reaction to light in preterm neonates. Issue 1 (January 1990) - Robinson, J; Fielder, A R
Abstract : The pupil controls the amount of light entering the eye. We have examined both the time course for the development of the light reflex and pupil diameter before and after this event in 50 neonates. The pupillary light reflex was absent in all neonates of less than 30 weeks' gestational age, it gradually developed from this age and by 35 weeks it was present in all. Several possible mechanisms that may explain the onset of this reflex are considered. Before the onset of the pupil reflex mean horizontal pupillary diameter was 3.46 mm compared with 3.02 mm after the reflex development. We have estimated the amount of light reaching the retina (retinal irradiance) for preterm neonates and although it is less than that known to cause retinal damage in animals, further research is necessary to determine whether early light exposure has an adverse or beneficial effect on the immature visual system.